Organizational studies and complexity: Stacey and Morin - Boeira, Sérgio Luis; Inácio, Ana Elise Cardoso; Stürmer, Jorge Altair Pinto (Revista de Administração da UFSM, 2019)
This theoretical essay aims to identify some approaches to the complexity of comparing contributions of internationally renowned authors as a reference in organizational studies, such as Stacey and Morin. In the literature that deals with the theme of complexity, many similar concepts are observed; several contributions of authors, some trained in natural sciences, others in the human sciences and philosophy. It is a theme that is recognized both inter and transdisciplinary, and it has been gaining pulse since the 1980’s. The conclusion is that Stacey and Morin have significantly contributed to the understanding of the organizational process and the differences between their approaches can be understood by comparing their life experiences and academic training. Furthermore, it is evident that overtime Stacey supports the critical and broad approach advocated by Morin complexity. On the one hand, while Stacey remains in the social sciences, Morin articulates social sciences as well as biophysics and philosophy. Regarding existing disputes in the field of complexity studies, this comparison indicates an improvement from the perspective of complexity intelligence (Latin culture) over the angle of complex adaptive systems (Anglo - Saxon culture).